2002
DOI: 10.1067/mcp.2002.127396
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of diltiazem and its metabolites in relation to CYP2D6 genotype

Abstract: CYP2D6 activity does not have a major impact on the disposition of diltiazem. In contrast, desacetyl diltiazem and N-demethyldesacetyl diltiazem are markedly accumulated in individuals expressing a deficient CYP2D6 phenotype. Because these metabolites exhibit pharmacologic properties of possible importance, individual CYP2D6 activity might be an aspect to consider in the clinical use of diltiazem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Considering that R-125528 itself could not be excreted into the bile or urine as an intact form, the -1 oxidation mediated by CYP2D6 was considered to be a crucial pathway for the elimination of R-125528 from the systemic circulation. CYP2D6 is one of the best known P450 isoforms that leads to large interindividual variations in drug concentration, drug response, therapeutic outcome, and/or toxicity because of its polymorphic nature (Brynne et al, 1998;Molden et al, 2002;Fux et al, 2005). The variability in CYP2D6 activity is mainly determined genetically, and 5 to 10% of Caucasians are reported to express a poor CYP2D6-metabolizing phenotype, resulting from the inheritance of two mutant null alleles (van der Weide and Steijns, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that R-125528 itself could not be excreted into the bile or urine as an intact form, the -1 oxidation mediated by CYP2D6 was considered to be a crucial pathway for the elimination of R-125528 from the systemic circulation. CYP2D6 is one of the best known P450 isoforms that leads to large interindividual variations in drug concentration, drug response, therapeutic outcome, and/or toxicity because of its polymorphic nature (Brynne et al, 1998;Molden et al, 2002;Fux et al, 2005). The variability in CYP2D6 activity is mainly determined genetically, and 5 to 10% of Caucasians are reported to express a poor CYP2D6-metabolizing phenotype, resulting from the inheritance of two mutant null alleles (van der Weide and Steijns, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, diltiazem is primarily metabolized to N-demethyldiltiazem, O-demethyldiltiazem, and deacetyldiltiazem by CYP3A4, CYP2D6, and esterase(s), respectively (Molden et al, 2002;Williams et al, 2002); however, the esterase(s) responsible for the deacetylation remained to be identified. Yeung et al (1990) reported that the AUC ratio of deacetyldiltiazem to diltiazem after an oral dose of diltiazem was much higher in rats (0.82) than in humans (0.12), suggesting the existence of species differences in the enzyme activity and/or substrate specificity of the esterase(s) involved in diltiazem deacetylation.…”
Section: Discussionmentioning
confidence: 99%
“…1) (Yeung et al, 1990;Molden et al, 2002). N-demethylation and deacetylation are the major metabolic pathways, and the area under the curve (AUC) ratio of O-demethyldiltiazem, deacetyldiltiazem, and N-demethyldiltiazem reported in humans was 1:3.4:28, respectively (Molden et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2D6 is one of the best known P450 isoforms and leads to large interindividual variations in drug concentration, drug response, therapeutic outcome, and/or toxicity because of its polymorphic nature (Brynne et al, 1998;Molden et al, 2002;Fux et al, 2005). Although CYP2D6 is a minor component (ϳ2%) of the total P450 content in the human liver, many drugs currently in clinical use are metabolized by CYP2D6, such as antiarrhythmics, antidepressants, antipsychotics, ␤-blockers, and analgesics (Jones et al, 1997).…”
mentioning
confidence: 99%